PELAKSANAAN PRINSIP MENGENAL NASABAH DALAM MENCEGAH TINDAK PIDANA PENCUCIAN UANG DI PT BANK MAYAPADA TBK SURAKARTA - TOMIARSO, DODIE FAJAR (Dinamika Hukum, 2019)
The principle of knowing Know Your Customer Principle (KYCP) customers at PT. Bank Mayapada Tb Surakarta, simply by including name, address and no. telephone, but now it's not because every stamp filling transaction must be complete with ID / SIM number, occupation / business field, position, place of birth date, source of funds, transfer requirements and relationship with the recipient of the transfer. Filling out the data above is to fulfill the Know Your Customer Principles in accordance with Bank Indonesia Regulation Number 3/231 / PB17 / 2001 on December 13, 2001 which is an improvement and previous regulation, namely Bank Indonesia Regulation Number 3/10 / PBI / 2001 on June 18 2001 about the same thing. In 2004 it was the third year in applying this principle. In principle, this Regulation states that mandatory PJKs to apply the Customer Introduction Principle to know not only their identity but also include reporting suspicious transactions. Bank Indonesia is obliged to investigate the origin of its customers. The implementation of the principle of knowing your customers (know your customer principles) cleanses customer data, makes a report on the implementation of the principle of knowing customers every month, socializing the principle of knowing customers in all branches and all employees of PT. Bank Mayapada Tb Surakarta, verify customer data, monitor customer transactions, cooperate with law enforcement officials and report if there is a suspicious transaction at PT. Bank Mayapada Tb Surakarta. Keywords: Know Your Customer Principles, Prevention, Money Laundering Crimes